Water Stress Responses of Tomato Mutants Impaired in Hormone Biosynthesis Reveal Abscisic Acid, Jasmonic Acid and Salicylic Acid Interactions - Muñoz-Espinoza, Valeria A.; López-Climent, María F.; Casaretto, José A.; Gómez-Cadenas, Aurelio (Frontiers in Plant Science, 2015)
To investigate the putative crosstalk between JA and ABA in Solanum lycopersicum plants in response to drought, suppressor of prosystemin-mediated responses2 (spr2, JA-deficient) and flacca (flc, ABA-deficient) mutants together with the naphthalene/salicylate hydroxylase (NahG) transgenic (SA-deficient) line were used. Hormone profiling and gene expression of key enzymes in ABA, JA and SA biosynthesis were analyzed during early stages of drought. ABA accumulation was comparable in spr2 and wild type (WT) plants whereas expression of 9-cis-epoxycarotenoid dioxygenase 1 (NCED1) and NCED2 was different, implying a compensation mechanism between NCED genes and an organ-specific regulation of NCED1 expression. JA levels and 12-oxo-phytodienoic acid reductase 3 (OPR3) expression in flc plants suggest that ABA regulates the induction of the OPR3 gene in roots. By contrast, ABA treatment to flc plants leads to a reduction of JA and SA contents. Furthermore, different pattern of SA accumulation (and expression of isochorismate synthase and phenylalanine ammonia lyase 1) was observed between WT seedlings and mutants, suggesting that SA plays an important role on the early response of tomato plants to drought and also that JA and ABA modulate its biosynthesis. Finally, hormone profiling in spr2 and NahG plants indicate a crosstalk between JA and SA that could enhance tolerance of tomato to water stress.